Training and Counseling on Stock Opname Bookkeeping at Saung Injuk Restaurant, Bandung Regency - Erislan Erislan (Jurnal Syntax Admiration, 2024)
Community Service Activities that provide counseling on the importance of bookkeeping and training on bookkeeping and hospitalization recording for all incoming and outgoing goods activities to maintain the continuity of stock and raw material availability as well as cost efficiency efforts. The outcome that can be realized from this Community Service activity is that actors are able to carry out bookkeeping and recording of their business regularly by using hospitalization recording and calculating cost efficiency. Recording of stock-taking. As a result, "Saung Injuk Restaurant" has been done by the owner but only for ordering raw materials based on the remaining stock. 2) There has not been recorded a match between the initial number of products and after being sold which is then confirmed with the remaining stock. 3) There is a risk that the goods sold with the initial stock do not match the remaining stock.